Dynamics and hydration of the active sites of mammalian cytochromes P450 probed by molecular dynamics simulations - Hendrychova, Tereza; Berka, Karel; Navratilova, Veronika; Anzenbacher, Pavel; Otyepka, Michal (Current drug metabolism, 2012)
The flexibility, active site volume, solvation, and access path dynamics of six metabolically active mammalian cytochromes P450 (human 2A6, 2C9, 2D6, 2E1, 3A4 and rabbit 2B4) are extensively studied using molecular dynamics (MD) simulations. On average, the enzymes' overall structures equilibrate on a 50+ ns timescale. The very open CYP2B4 structure closes slowly over the course of the simulation. The volumes of the active sites fluctuate by more than 50% during the MD runs; these fluctuations are mainly due to movements of the main chains, with only a handful of amino acid residues in CYP2B4, CYP2D6, CYP2A6 and CYP2C9 showing significant independent side chain movement. The volume of the active site of CYP2E1 fluctuates heavily, ranging from 220 to 1310 A(3), due to the opening and closing of gates to two adjacent cavities. CYP2E1 has the least hydrated active site of the studied CYPs; this is consistent with its preference for non-polar substrates. The CYP2A6 and CYP2E1 active sites are deeply buried, with access paths that are narrower than the radius of a water molecule. However, waters are still able to access these active sites due to local adaptations of the channel to accommodate their passage. This finding may imply that the access paths of the CYPs never fully open prior to contact with the substrate; instead, the substrate may induce adaptive conformational changes during its passage to the active site. This may also explain why some substrate recognition sites are localized along individual enzymes' access paths.
Keywords: simulace molekulární dynamiky; systém (enzymů) cytochromů P-450; zvířata; Humans; Rabbits; králíci; Molecular Dynamics Simulation; katalytická doména; Cytochrome P-450 Enzyme System; Catalytic Domain; lidé; Animals